18.4k views
3 votes
What is the answer to -t=9(t -10)

User Aqeel Raza
by
5.4k points

1 Answer

3 votes

Answer: The answer to this question is t=9

Step-by-step explanation: This is the linear equation, to solve it we have to simplify the like terms.

-t= 9(t-10)

-t=9t-90

-10t=-90

t= 9

On the right hand side multiply through out by 9 and move 9t to the other side it will change side.

Then divide both sides by -10

User Minem
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.